Effects of measurement methods and growing conditions on phenotypic expression of photosynthesis in seven diverse rice genotypes - Reavis, Megan; Purcell, Larry C.; Pereira, Andy; Naithani, Kusum (Frontiers in Plant Science, 2023)
Light response curves are widely used to quantify phenotypic expression of photosynthesis by measuring a single sample by sequentially altering light intensity within a chamber (sequential method) or on different samples that are each acclimated to a different light level (non-sequential method). Both methods are often conducted in controlled environments to achieve steady-state results and neither method involves equilibrating the entire plant to the specific light level. Here, we compare sequential and non-sequential methods in controlled (greenhouse), semi-controlled (plant grown in growth chamber and acclimated to field conditions 2-3 days before measurements), and field environments. We selected seven diverse rice genotypes (five genotypes from the USDA rice mini-core collection: 310588, 310723, 311644, 311677, 311795; and 2 additional genotypes: Nagina 22 and Zhe 733) to understand (1) the limitations of different methods, and (2) phenotypic plasticity of photosynthesis in rice grown under different environments. Our results show that the non-sequential method was time-efficient and captured more variability of field conditions than the sequential method, but the model parameters were generally similar between two methods except the maximum photosynthesis rate (Amax). Amax was significantly lower across all genotypes under greenhouse conditions compared to the growth chamber and field conditions consistent with prior work, but surprisingly the apparent quantum yield (𝛼) and the mitochondrial respiration (Rd) were generally not different among growing environments or measurement methods. Our results suggest that field conditions are best suited to quantify phenotypic differences across different genotypes and non-sequential method was better at capturing the variability in photosynthesis.